Solution conformation of the major adduct between the carcinogen (+)-anti-benzo[a]pyrene diol epoxide and DNA. - Cosman, M (1992)
We have synthesized, separated, and purified approximately 10 mg of a deoxyundecanucleotide duplex containing a single centrally positioned covalent adduct between (+)-anti-benzo[a]pyrene (BP) diol epoxide and the exocyclic amino group of guanosine. Excellent proton NMR spectra are observed for the (+)-trans-anti-BP diol epoxide-N2-dG adduct positioned opposite dC and flanked by G.C pairs in the d[C1-C2-A3-T4-C5-(BP)G6-C7-T8-A9-C10-C11].d[12- G13-T14-A15-G16-C17-G18-A19-T20-G 21-G22] duplex +ADdesignated (BP)G.C 11-mer+BD. We have determined the solution structure centered about the BP covalent adduct site in the (BP)G.C 11-mer duplex by incorporating intramolecular and intermolecular proton-proton distance bounds deduced from the NMR data sets as constraints in energy minimization computations. The BP ring is positioned in the minor groove and directed toward the 5' end of the modified strand. One face of the BP ring of (BP)G6 is stacked over the G18 and A19 sugar-phosphate backbone on the partner strand and the other face is exposed to solvent. A minimally perturbed B-DNA helix is observed for the d[T4-C5-(BP)G6-C7-T8].d[A15-G16-C17-G18-A19] segment centered about the adduct site with Watson-Crick alignment for both the (BP)G6.C17 pair and flanking G.C pairs. A widening of the minor groove at the adduct site is detected that accommodates the BP ring whose long axis makes an angle of approximately 45 degrees with the average direction of the DNA helix axis. Our study holds future promise for the characterization of other steroisomerically pure adducts of BP diol epoxides with DNA to elucidate the molecular basis of structure-activity relationships associated with the stereoisomer-dependent spectrum of mutational and carcinogenic activities.